Badan Sosial Lintas Agama (BASOLIA) - Rully Antonius Haryanto (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2019)
This article discusses some efforts performed by an inter-religious movement called Basolia and its contribution to the harmony of religious life in Bogor. This study aims to explain strategies and tactics carried out by the activists of Basolia, to analyse factors supporting or blocking the religious dialogue movement of Basolia, and to know the contribution of Basolia for making religious harmony in Bogor. This research found that Basolia provides for making harmony in Bogor through social activities initiated by interfaith figures, lay people, and organizations. The involvement of religious figures, lay people, and organization has strengthened social ties between peoples and communities in Bogor, which is remarkable for making harmony.